High quality single-crystalline aluminum nitride grown using pulsed atomic-layer Epitaxy technique by MOCVD on sapphire substrate / Mohd Nazri Abd Rahman - Mohd Nazri , Abd Rahman (2021)
The unique structural properties and engineering characteristics of nitride-based materials have given them a special position in semiconductor applications. Alloys with a tuned energy bandgap from ultraviolet to infrared wavelengths are possible to be deposited in maintaining the wurtzite crystal structure. However, the aluminum nitride / aluminum gallium nitride (AlN/AlGaN) based hetero-structures for deep-ultraviolet (DUV) emitters as well as AlN-based actuators and piezoelectric sensors are highly inefficient owing to the excessive mismatch in thermal and lattice features between these epilayers with flat c-plane sapphire substrates, resulting in crack formation and high dislocation densities. This thesis mainly focuses on the development of high-quality single-crystalline AlN epilayer at relatively low growth temperature and at standard pressure on c-plane sapphire substrate by metal organic chemical vapor deposition (MOCVD). This thesis mainly covers the examinations of as-deposited AlN films on c-plane sapphire substrates at relatively low growth temperature and standard pressure using pulsed atomic-layer epitaxy (PALE) techniques and evaluates the effects of growth conditions towards the as-deposited PALE AlN films. The results are based on atomic force microscopy (AFM), field emission scanning electron microscopy (FESEM), Raman spectroscopy, photoluminescence (PL) spectroscopy, high-resolution X-ray diffractometer (HR-XRD) and X-ray photoelectron spectroscopy (XPS). For the deposition of AlN films at relatively low growth temperature using PALE growth techniques, it was demonstrated that the optimization of PALE AlN deposition temperature, AlN nucleation layer (NL) growth temperature, number of pulse cycle, and the flow of ammonia (NH3) flux density during deposition have an immense effect towards the growth mechanism and its physical properties. Defects were examined morphologically, structurally and optically in the as-deposited PALE AlN films which then been described in detail. The initial growth conditions were delineated to be crucial for the final quality of the PALE AlN film. A 2-micrometer thick with a near-atomically flat of 0.87 nm root mean square surface roughness and crack-free surface of as-deposited PALE AlN films has well been obtained in the end of this thesis. Additionally, a high crystal quality of as-deposited PALE AlN films was recorded with the lowest threading dislocation density of 1.50 x 107 cm-2 for screw dislocation and 3.70 x 109 cm-2 for mixed-edge dislocation. The mechanism of strain relief was described using the in-plane strain analysis with Raman spectroscopy and correlated with each type of defect that was found in the PALE AlN films. The lowest in-plane stress and strain was recorded at 0.195 GPa and 0.042%, respectively. Moreover, the PL and XPS survey scan revealed the low incorporation of oxygen impurity in the as-deposited PALE AlN films surface. Finally, a crack-free with high crystal quality and atomically-flat surface of AlN template was achieved on c-plane sapphire substrate at relatively low growth temperature and standard pressure using PALE growth techniques via MOCVD. This thesis enclosed the possibility to perform a high quality single-crystalline AlN epilayer grown at relatively low temperature and at standard pressure without the needs of additional ex-situ high-technology instrument as per compared to other research group.